Transmedia-organizing in preventing/countering violent extremism (P/CVE) initiatives in Indonesia - Widjanarko, Putut; Chusjairi, Juni Alfiah (Interaksi: Jurnal Ilmu Komunikasi, 2025)
Religiously motivated radical extremism has been a major source of concern around the world, including Indonesia. Governments, communities, and civil society organizations (CSOs) are launching a variety of initiatives to prevent and combat violent extremism (P/CVE), including the use of various media platforms. This study looks at how two CSOs in Indonesia, Kreasi Prasasti Perdamaian (KPP) and Peace Generation (PeaceGen), handle various media (transmedia organizing) in P/CVE initiatives. Data collection included (1) in-depth interviews with each CSO's team members, (2) observation of some of their activities, and (3) document analysis of various media products. The findings of this study show that the transmedia organizing of both CSOs has paved the way for increased participation from the movement base, thereby strengthening social movement identity. This research contributes to the view of the critical role and understanding of the media in preventing and counteracting violent extremism due to the increasingly strong influence of the media in everyday life and the fact that terrorist and radical organizations also use the media for propaganda and recruitment.